The Effect of Additional Income for State Civil Apparatus Employees (Incentives) on the Performance of Civil Servants at the Regional Inspectorate Office of West Kutai Regency - Elvi Elvi; Musmuliadi Musmuliadi; Agustinus Djiu (International Journal of Social Service and Research, 2022)
This research begins with the problem that the performance of the West Kutai Regional Inspectorate Office is not right on target, there is no data on the number of damaged roads, while the additional income of state civil servants (incentives) has been increased by 100%. The purpose of this study was to determine the effect of additional income for state civil servants (incentives) on the performance of civil servants at the West Kutai Regional Inspectorate Office. In this study, the researcher uses the Mangkunegara theory which states that incentives are a form of motivation expressed in the form of money on the basis of high performance and also an award in the form of incentives on the basis of high work performance, which is a sense of recognition from the agency towards employee performance and contributions to the agency. The results of the study show that the performance analysis produced by civil servants at the West Kutai Inspectorate Office based on research has a significant effect. While the effect of additional income of state civil servants (incentives) on the performance of civil servants at the West Kutai Inspectorate Office can be said to have a positive and significant effect with a percentage of 49.7% while the remaining 50.3% is influenced by other factors not examined in this study.